Temperature and substrate for the germination test of physic nut seeds - Martins, Cibele Chalita [UNESP]; Machado, Carla Gomes [UNESP]; Cavasini, Raquel [UNESP] (FapUNIFESP (SciELO), 2008)
Official rules for seed analysis don t establish criteria to execute germination tests for all species. This way, the aim of this research was to determinate the substrate, temperature and counting time for the germination test of physic nut seeds. For the germination test, four replications of 20 seeds were used, evaluating daily the normal seedlings until the end of germination. Initially, the substrates with sowing in vermiculite, were evaluated in rolled paper towels, in sand and in soil using alternating temperature of 20-30°C. The most favorable substrates for germination were evaluated with another stage, using constant temperatures of 25, 30 and 35°C and alternating ones, of 15-35°C, 20-35°C and 20-30°C. One concluded that the germination test of physic nut seeds must be performed with the alternating temperature of 20-30°C in sand or paper towel and with final counting 10 days after sowing.
Temperatura e substrato para o teste de germinação de sementes de pinhão-manso
Keywords: Fisiological quality seeds; Jatropha curcas L.; Oil crop